Late Quaternary palaeogeographic evolution of the mid western coastal zone of Naxos Island (Cyclades, Greece). - Maroukian, H.; Gaki-Papanastassiou, K.; Evelpidou, N.; Vassilopoulos, A. (6th International Conference on Geomorphology, 2005)
Naxos is the biggest island of the Cyclades. It is composed primarily of mica-shists, gneiss and marbles and granodiorites in the western part. The latter extend along parts of the studied area. Detailed coastal geomorphological study and GIS analysis made possible the determination of coastal evolution of this area during Late Quaternary. A number of shallow drillings and archaeological evidence helped in the determination of the sequence of the coastal evolution of the study area. Two sets of coastal dunes were mapped reaching elevation of 4 and 8 m respectively, plus older well preserved dune fields reaching elevations up to 18m located in the south. It was found that three granodiorite capes were small islands at the end of the last transgression in Mid Holocene. Since then, parts of the coastline, prograded joining them and forming coastal dunes, beachrocks and wetlands in several locations.